(untitled) (Eurasian Scientific Herald, 2022)
The paper notes that the use of multimedia technologies in a foreign language lesson is very large, since the virtual environment of the Internet allows us to go beyond time and space, giving its users the opportunity to communicate with real interlocutors on relevant topics. The classification of multimedia teaching aids is given, we combine them into groups depending on the methodological and functional purpose.